Analisis Biaya Langsung dan Biaya Tidak Langsung Penderita Hipertensi pada Masyarakat Wilayah Hutan Tropis Lembap di Kota Samarinda - Chaerunnisa AR; Ratno Adrianto; Reza Nur Fahmi; La Suhani (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Hypertension is the leading non-communicable disease (NCD) in Samarinda City, imposing a considerable economic burden on patients and their families. This study aimed to analyze direct and indirect costs borne by hypertension patients in the humid tropical forest area of Samarinda City. A quantitative descriptive observational study with a cross-sectional design was conducted involving 370 respondents recruited via purposive sampling from 10 community health centers (Puskesmas) across Samarinda. Data were collected through structured interviews covering direct costs (outpatient fees, inpatient expenses, and other out-of-pocket medical costs) and indirect costs (transportation, assistive devices, and productivity loss for both patients and caregivers). Results showed that the average annual direct cost per patient was IDR 1,236,345, dominated by routine outpatient and alternative treatment expenses. The average annual indirect cost was IDR 2,177,808, with productivity loss being the largest component. Indirect costs significantly exceeded direct costs, highlighting the hidden economic burden of hypertension. All respondents were JKN/BPJS participants, yet out-of-pocket expenditures remained substantial. These findings emphasize the need for comprehensive hypertension control programs that address both medical and non-medical economic burdens.